1982
DOI: 10.1111/j.1439-0329.1982.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Picea sitchensis and Pinus contorta stumps by basidiospores of Heterobasidion annosum

Abstract: Infection of Pinus contorta and Picea sitcbensis stumps by basidiospores of Heterobasidion annosum is extremely variable, both within and between sites, but in general P. sitchensis stumps are less susceptible than those of P. contorta. Measurement of the cross-sectional area occupied by H. annosum on each stump provides a more sensitive test of species susceptibility than assessment of the proportion of stumps infected. P. sitchensis stumps become infected on a variety of soils but there is evidence to sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
(7 reference statements)
4
27
0
Order By: Relevance
“…In common with similar studies of stump colonization (REDFERN 1982(REDFERN , 1993REDFERN et al 1997), this study recorded large within factor variation for both incidence and area colonized. This variation may have obscured differences within factors such as season and biogeoclimatic subzone.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In common with similar studies of stump colonization (REDFERN 1982(REDFERN , 1993REDFERN et al 1997), this study recorded large within factor variation for both incidence and area colonized. This variation may have obscured differences within factors such as season and biogeoclimatic subzone.…”
Section: Resultssupporting
confidence: 79%
“…Precipitation as rainfall could affect spore infection of stumps by washing spores from the air (REYNOLDS and WALLIS 1966) and by washing spores from the stump surface before infection can occur (REDFERN 1982). However, availability of spores appears not to have a major effect on incidence of H. annosum because stumps became infected in the wettest seasons and subzones in this study, and REDFERN (1993) found that covering stumps for 24 h after inoculation did not result in a high incidence of infection in a high rainfall area.…”
Section: Discussionmentioning
confidence: 99%
“…High variability in area of colonized stump wood has been noted even in artificially basidiospore-inoculated stumps, as e.g. of Sitka spruce (0.02-56.6%) (Morrison and Redfern 1994) and lodgepole pine (3-96%) (Redfern 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Meredith (1959) used the same concentration, and Kuhlman & Hendrix (1964) used 1.4 x 1.0 3 viable spores ml" 1 . Redfern (1982Redfern ( , 1993 used suspensions containing up to 160 x 10 4 viable spores ml" 1 , equivalent to 1090 x 10 4 spores dm" 2 of stump surface. Direct comparison of these figures with the effective inoculum dose from natural sources is not feasible because this depends on the period during which stump surfaces remain receptive to spores.…”
Section: Introductionmentioning
confidence: 99%